Centros urbanos e espaços livres públicos: produção e apropriação em Palmas-TO - Oliveira, Lucimara Albieri de (Universidade Federal de São Paulo, 2017)
This thesis investigates the urban centers and the phenomenon of centralities today, having Palmas, capital of Tocantins State, as the empirical object. Palmas was established, for a still non-existent population, from an urban plan of 1989. Its project rationality precepts are already transgressed in its early years, when it actually enters the capitalist logic of urban space production, and the public administration acts as a key participant in such process. As a result, it triggers the phenomenon of early multi centrality. Its urban centers arise triggering social contradictions, while exposing its urbanization process conflicts. While its main center symbolically evokes the power and is aligned to the hegemonic interests, its popular sub-centers reveal a collective construction of space and rich appropriations of its public open spaces, opening up greater possibilities for urban living and contributing to the formation of citizenship.